2010
DOI: 10.1161/hypertensionaha.109.144428
|View full text |Cite
|
Sign up to set email alerts
|

Renal Medullary MicroRNAs in Dahl Salt-Sensitive Rats

Abstract: Abstract-MicroRNAs are endogenous repressors of gene expression. We examined microRNAs in the renal medulla of Dahl salt-sensitive rats and consomic SS-13 BN rats. Salt-induced hypertension and renal injury in Dahl salt-sensitive rats, particularly medullary interstitial fibrosis, have been shown previously to be substantially attenuated in SS-13 BN rats. Of 377 microRNAs examined, 5 were found to be differentially expressed between Dahl salt-sensitive rats and consomic SS-13 BN rats receiving a high-salt diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
155
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(164 citation statements)
references
References 41 publications
(91 reference statements)
9
155
0
Order By: Relevance
“…In cell lines from heart, lung, and kidney with TGF-treatment, overexpression of miR-29 suppresses but inhibition of miR-29 promotes expression of fibrotic markers [70,74,75,[78][79][80][81]. Gene delivery of miR-29b either before or after established obstructive nephropathy successfully blocks progressive renal fibrosis in a mouse model of unilateral ureteral obstruction nephropathy [74], providing a strong support of anti-fibrotic properties of miR-29.…”
Section: Mir-29mentioning
confidence: 89%
See 1 more Smart Citation
“…In cell lines from heart, lung, and kidney with TGF-treatment, overexpression of miR-29 suppresses but inhibition of miR-29 promotes expression of fibrotic markers [70,74,75,[78][79][80][81]. Gene delivery of miR-29b either before or after established obstructive nephropathy successfully blocks progressive renal fibrosis in a mouse model of unilateral ureteral obstruction nephropathy [74], providing a strong support of anti-fibrotic properties of miR-29.…”
Section: Mir-29mentioning
confidence: 89%
“…Gene delivery of miR-29b either before or after established obstructive nephropathy successfully blocks progressive renal fibrosis in a mouse model of unilateral ureteral obstruction nephropathy [74], providing a strong support of anti-fibrotic properties of miR-29. Results from heart, lung, and kidneys also demonstrate that the anti-fibrotic effects of miR-29 are mediated through its ability to suppress the ECM-related gene transcription because more than 20 different ECM-related genes have been validated as direct targets of miR-29 by reporter gene assays and some of them are induced by TGF-signaling [75,80,82].…”
Section: Mir-29mentioning
confidence: 98%
“…Plasma miR-29a was a new biomarker that could play a role in the pathophysiology of atherosclerosis (Hulsmans and Holvoet 2013). Previous studies (Liu et al 2010;Maurer et al 2010;Kriegel et al 2012) have revealed that target genes of miR-29, such as type I and type III collagens, were important in the development of atherosclerosis (Ulrich et al 2016). The usage of miR-29 antagonists may prevent plaque remodelling (Ulrich et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…77 Predicted conserved binding sites for the miR29a-c family on the 3 0 -UTR of 20 collagen genes have been identified. 78 This property is unique to the miR-29 family because the predicted binding sites of the collagen genes are not attributed to any sequence homology in their 3 0 -untranslated region. 78 In adults, members of the miR-29 family cause suppression of ECM genes, resulting in tissue repair with a scar.…”
Section: Mirna and Regenerative Medicinementioning
confidence: 99%
“…78 This property is unique to the miR-29 family because the predicted binding sites of the collagen genes are not attributed to any sequence homology in their 3 0 -untranslated region. 78 In adults, members of the miR-29 family cause suppression of ECM genes, resulting in tissue repair with a scar. Dysregulation of ECM caused by lower miR-29 is associated with fibrosis development in several organs, including the heart, 77 kidney, 79 lung, 80 and liver.…”
Section: Mirna and Regenerative Medicinementioning
confidence: 99%